KAJIAN PEMONDOKAN PUTRI YANG TINGGAL DI SEKITARAN KAMPUS UNIVERSITAS RIAU PANAM PEKANBARU - Ramadiah, Ratna; ", Basri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research is done at daughter lodging around Riau Panam Pekanbaru's University campus correct it at Hamasah's Lodging. This research intent know factor that regards to motivate coed reads Al-Quran and impact to afters coed read Al-Quran. This research is entitled “Daughter Housing study That Lives In one cycle of Riau Panam Pekanbaru's University Campus ”. Observational subject problem it is whatever factor which regard coed motivation reads Al-Quran and how impact to afters coed read Al-Quran. Sample take in observational it is with Saturated Sampling tech or census. total sample which is 15 person and to key informan which is 1 person. Method that is utilized is kualitatif's Descriptive method with kualitatif's data analysis. Data winnow instrument that is utilized is observation, visceral interview and documentation. Observational result in common that is done therefore researcher concludes: Factor that regards coed to read Al-Quran which lives at Hamasah's lodging because of marks sense push of oldster and also of comate and wish of thyself. Push of oldster because they were inured read Al-Quran everyday at its house. Meanwhile marks sense push of friend as invitation in term positive in reads Al-Quran as well as while it lives at regulation aught lodging read Al-Quran and if mark sense push of itself since they constitute coed earlier one wonted with religion's activity at schooled previous and also because wants changed get better. Impact marks sense to read Al-Quran everyday it can revamp self gets better, feeling calm and comfortable in heart and soul, getting folded reward double, as doctor in all liver disease kind, and dipermudahkan any kind at secular and most of umpteen informan has IP and IPK what do get worked up.Key word: Study, Daughter housing, Al-Quran.